Problem-based learning in Mastering Arabic Vocabulary in Modern Islamic Boarding Schools: Penerapan Problem Based Learning dalam Penguasaan Kosakata Bahasa Arab di Pondok Pesantren Modern - Abdul Hafidz bin Zaid; Diana Fitri Islami; Fairuz Subakir Ahmad; Agus Yasin (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
This study examines the role of the problem-based learning model in mastering mufradāt among 3 KMI at Islamic boarding schools. Using a descriptive qualitative approach, data were collected through classroom observations, interviews with teachers and language instructors, and a review of relevant documents. The results indicate that the implementation of PBL strengthened mastery of mufradāt through several indicators: an accurate understanding of word meanings, increased vocabulary use in oral responses, and a more consistent ability to construct sentences appropriate to the context. Changes in learning behaviour were also evident, such as more active participation, the ability to solve problems independently and in groups, and increased Confidence in speaking Arabic. The problem identification stage and the collaborative inquiry process were the most influential aspects. The context of language familiarisation, such as muhādarah and taʿbīr syafawī, enhanced the natural internalization of new words, forming a strong synergy with PBL. This research offers novelty by demonstrating the readiness of PBL to be integrated into the immersive learning culture of modern Islamic boarding schools, thereby making it an effective model for contextual mufradāt learning. Keywords: Modern Islamic Boarding Schools, Mufradāt, Problem Based Learning, Qualitative Study